2020
DOI: 10.3390/su12197851
|View full text |Cite
|
Sign up to set email alerts
|

The Difference of Knowledge and Behavior of College Students on Plastic Waste Problems

Abstract: Environmental education in the academic level is the most effective way to increase environmental awareness of college students particularly in handling plastic waste problems. This study aimed to compare the student’s knowledge and behavior on plastic waste problem between environmental science and social science students and to examine the correlation of knowledge and behavior to reduce plastic waste. Through survey of 98 students of National Chung Hsing University, Taichung, Taiwan, we compared the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
1
15
1
Order By: Relevance
“…The results of this study also support the theory of behavior change that the increase in knowledge will increase environmentally friendly attitudes that lead to proenvironmental behavior, precisely the willingness to reduce plastic use (Steg and Vleg, 2009). It also supports the research of Situmorang et al (2020) regarding behavioral differences in students majoring in environmental and social sciences. They find significant differences in behavior to reduce plastic use, which appears in the conduct of buying products with plastic packaging, preparing shopping bags, using return plastic bags, picking up own lunch boxes, and having food on-site to reduce single-use plastic packaging.…”
Section: Discussionsupporting
confidence: 77%
“…The results of this study also support the theory of behavior change that the increase in knowledge will increase environmentally friendly attitudes that lead to proenvironmental behavior, precisely the willingness to reduce plastic use (Steg and Vleg, 2009). It also supports the research of Situmorang et al (2020) regarding behavioral differences in students majoring in environmental and social sciences. They find significant differences in behavior to reduce plastic use, which appears in the conduct of buying products with plastic packaging, preparing shopping bags, using return plastic bags, picking up own lunch boxes, and having food on-site to reduce single-use plastic packaging.…”
Section: Discussionsupporting
confidence: 77%
“…In general, lifestyle refers to the unique way of living which the overall society or a specific smaller population adopt [25]. This definition has commonly been employed by subsequent studies on lifestyle-related green behavior [26][27][28][29][30]. Consumer lifestyle applications is a commonly discussed topic among researchers, including both consumer and market-oriented approaches.…”
Section: Food-related Lifestyles (Frls) 221 Definition Of Lifestylementioning
confidence: 99%
“…Within universities, the authors of [10] examined students' knowledge on plastic waste problems using a survey of 98 students from a Taiwanese university. They found that students majoring in environmental sciences have a higher knowledge relative to social science majors.…”
Section: Literature Reviewmentioning
confidence: 99%